Tribological properties and hydrolysis stability study of benzothiazole borate derivative. (21st June 2013) - Zhongyi, He; Liping, Xiong; Liang, Qian; Sheng, Han; Aixi, Chen; Jianwei, Qiu; Xisheng, Fu
ABSTRACT A novel borate ester derivative containing mercaptobenzothiazol and ethanolamine group (BMB) was synthesised and characterised. Its tribological properties in RSO were evaluated using a four‐ball tribometer, and its action mechanisms were investigated by scanning electron microscopy and X‐ray photoelectron spectroscopy. Its hydrolysis stability was investigated by open observation method and half‐time method, and its mechanism was discussed through Gaussian calculation. Results show that BMB possesses excellent extreme pressure, better anti‐wear performances and excellent hydrolysis stability for lone electron of nitrogen atoms forming a coordination effect with B atom. The boundary film, which contains organic nitrogen and inorganic salt, such as BN, Fe2(SO4)3 and Fe‐O‐B, contributed to improve the tribological properties of RSO. Copyright © 2013 John Wiley & Sons, Ltd.